Myths and Facts About Inequality - Marcel Fratzscher (Intereconomics, 2018)
Germany's social contract, its 'social market economy' for the past seven decades, has aimed at spreading wealth and providing a broad social safety net for all groups of society. Yet a defining feature of Germany's new economy has been the sharp increase in inequality.
Keywords: 330